Pengaruh Konsentrasi Besi dalam Larutan Hara terhadap Gejala Keracunan Besi dan Pertumbuhan Tanaman Padi - Noor, Aidi; Lubis, Iskandar; Ghulamahdi, Munif; Chozin, Muhammad Achmad; Anwar, Khairil; Wirnas, Desta (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2012)
Iron (Fe) toxicity is a major constraint in rice production that decreases yield due to high level of soluble Fe. The aims of this experiement were to study the effect of particular Fe concentrations in nutrient solution on rice growth, and to determine Fe concentration in nutrient solution that caused light, moderate, and severe Fe toxiciy symptom. The experiment was conducted in a greenhouse, Bogor Agricultural University from May to July 2010. A randomized block design with two factors and three replications were used in this study. The first factor was Fe concentration in the medium solution (2, 50, 100, 200, 400, 600 ppm Fe), and second factor was rice genotypes (IR64, Margasari). The results showed the higher Fe concentration in the solution resulted in higher scores of iron toxicity symptoms, higher Fe levels in the plant, and caused stunted growth of rice plants. Levels of Fe in a solution of ≥ 200 ppm Fe inhibited plant growth. Iron toxicity symptom in Margasari was lower than the IR64 varieties, especially at concentrations of 200 and 400 ppm. According to the regression equation Y = 0.022X+ 1849, Fe concentration in the solution which caused light Fe toxicity symptom (score ≤ 3) was ≤ 52 ppm Fe, moderate (score = 5) was 143 ppm Fe, heavy (score = 7) was 234 ppm Fe, and severe (score ≥ 9) was ≥ 325 ppm Fe. Keywords: iron toxicity symptoms, iron concentration, rice